Aerosol radiative forcing over the south of Portugal: a combination of surface and satellite measurements - Santos, Dina (2012)
Aerosols directly affect the climate by increasing back-scattered radiation and by absorbing solar and long wave radiation. They indirectly affect climate by changing the microphysical properties of clouds and their life span, thereby modifying the planetary albedo and precipitation regime. However, the limited information on aerosol properties and dynamics, particularly in the troposphere, is a major uncertainty. In fact, the confidence in current climate change predictions is very low (IPCC, 2001), thus warranting detailed investigation of aerosols.